How Gylfi’s Illusion Breathes Life into the Sky - Sigurðsson, Gísli (Religionsvidenskabeligt Tidsskrift, 2022)
ABSTRACT: To date it has mostly been overlooked that the illusion in ‘Gylfi's Illusion’ is based on a metaphor, where what we can literally see in the sky is transformed into mythological phenomena through the magic of storytelling. By taking this idea at face value it becomes possible to look at the sky as a memory tool for the world of the gods. Thus everything we have above us in the sky has a mythological name and often a story attached to it, making it easier to remember all the details of the mythology as well as knowing your way around the sky. This approach to the mythology of Gylfaginning puts us on firm ground as we read it for what it is: a reflection of contemporary and traditional terminology about the sky as it was known to northern peoples from long before Christianity. RESUME: Hidtil er det blevet næsten overset, at illusionen i ’Gylfis illusion’ er baseret på en metafor, hvor det, vi bogstaveligt talt kan se på himlen, forvandles til mytologiske fænomener gennem fortælling. Ved at tage denne idé bogstaveligt bliver det muligt at se himlen som et hukommelsesværktøj for gudernes verden. Alt, hvad vi har over os på himlen, har således et mytologisk navn og ofte en historie knyttet til sig, hvilket gør det lettere at huske alle mytologiens detaljer samt at finde vej rundt på himlen. Denne tilgang til mytologien i Gylfaginning giver os fast grund under fødderne, når vi læser den for, hvad den er: en afspejling af samtidig og traditionel terminologi om himlen, som den var kendt af nordiske folk længe før kristendommen.